Sulfonated Beet Pulp as Solid Catalyst in One-Step Esterification of Industrial Palm Fatty Acid Distillate - Babadi, F.E.; Hosseini, S.; Masoudi Soltani, S.; Aroua, M.K.; Shamiri, A.; Samadi, M. (Springer Verlag (Germany), 2016)
In this research a new heterogeneous catalyst has been prepared for biodiesel production. The catalyst was prepared by sulfonating industrial sugar waste. Unlike homogeneous catalysts, which require further purification and separation from the biodiesel production reaction media, this inexpensive synthetic catalyst does not need to go through an additional separation process. This advantage consequently minimizes the total application costs. The catalyst was prepared by partially carbonizing sugar beet pulp at 400 °C. The carbonization product was then sulfonated with concentrated H2SO4vapor in order to produce a solid catalyst. The prepared catalyst was used in the esterification reaction between palm fatty acid distillate (PFAD) and methanol. The effects of the temperature, methanol/PFAD ratio, reaction time and catalyst dosage on the efficiency of the production were individually investigated. The optimum biodiesel production occurred at 85 °C, a reaction time of 300 min, catalyst dosage of 3 g and methanol/PFAD ratio of 5:1 (mol/mol), lowering the acid value from 198 to 13.1 (mg KOH/g oil) or the equivalent, with a fatty acid methyl ester yield of around 92 %. The results suggest that the synthesized inexpensive catalyst is useful for biodiesel production from PFAD.